(untitled) (Current Horticulture, 2024)
The experiment was conducted to find out the effect of branch bending with ten years on fruiting capacity, biomass and xylem vessel anatomical structure in walnut (Juglans regia L.) c.v. Xiangling and Qingxiang trees. Both the percentage of fertile fruits and nut yield were investigated in ten successive years from the trees being planted during 2008. And the biomass of trees and xylem vessel anatomical structure of annual semi-woody branches were measured during 2017. Although the response of both varieties was not similar, branch bending could increase the percentage of fertile fruits and nut yield only in early 3-6 years. In both varieties during ten years, branch bending reduced the trunk diameter above 20 cm ground, the width of vessel, vessel area and vessel total area/xylem transect area, increased the crown area and dry weight of above-ground significantly, but had no effect on above-ground and under-ground fresh weight. There were no more positive effects of branch bending in long-term cultivation of Xiangling and Qingxiang walnuts. It seems that more physiological responses need to be concerned to evaluate the long-term effects of branch bending.